“ABC”—The Awareness-Body-Chart: A new tool assessing body awareness - Danner, Ursula (PLoS One, 2017)
BACKGROUND: Despite the importance of body awareness for health and well-being there is still a lack of valid assessment tools to scan proper body awareness. To respond to the limitations of questionnaires (reading/interpretation problems) the Awareness-Body-Chart (ABC) was designed to assess body awareness by colouring 51 regions according to their awareness. The objective of this study was to investigate the psychometric characteristics of the ABC. METHODS: In a questionnaire-study, 106 students in Graz (79 females, 27 males, age median 21 (IQR 20–23) years) filled in the ABC, furthermore a German body awareness questionnaire „KEKS”, and the Beck Depression Inventory II. Factor structure, internal consistency, and retest reliability of the ABC were investigated. Correlations of the ABC with the KEKS and the Beck Depression Inventory II and comparisons of subgroups were conducted. RESULTS: Through factor analyses, 14 factors with clear assignments to body parts could be categorized: cranium, face, cervical/lumbar region, chest/abdomen, back, shoulder, upper arm, lower arm/elbow, hand, genital area, thigh/hip, knee, lower leg, and foot. The 14 body parts and the total score showed acceptable to high Cronbach’s alphas (α = .64 - .97). The test-retest reliability showed values between ρ = .71 and ρ = .96. The correlation of the ABC and KEKS (r = .66, p < .001) confirmed validity. Further indications of validity could be seen in comparisons of subgroups and in correlations with the Beck Depression Inventory II. CONCLUSION: The ABC proved good psychometric properties with acceptable to high internal consistency, acceptable to high retest reliability and high construct validity. It is an easy-to-use tool for clinical settings and research. The ABC opens new insights into body awareness-patterns of various subgroups.